Non-coding RNA: A key regulator in the Glutathione-GPX4 pathway of ferroptosis - Sadique Hussain; Gaurav Gupta; Moyad Shahwan; Pooja Bansal; Harpreet Kaur; Mahamedha Deorari; Kumud Pant; Haider Ali; Sachin Kumar Singh; Venkata Sita Rama Raju Allam; Keshav Raj Paudel; Kamal Dua; et al. (Non-coding RNA Research)
Ferroptosis, a form of regulated cell death, has emerged as a crucial process in diverse pathophysiological states, encompassing cancer, neurodegenerative ailments, and ischemia-reperfusion injury. The glutathione (GSH)-dependent lipid peroxidation pathway, chiefly governed by glutathione peroxidase 4 (GPX4), assumes an essential part in driving ferroptosis. GPX4, as the principal orchestrator of ferroptosis, has garnered significant attention across cancer, cardiovascular, and neuroscience domains over the past decade. Noteworthy investigations have elucidated the indispensable functions of ferroptosis in numerous diseases, including tumorigenesis, wherein robust ferroptosis within cells can impede tumor advancement. Recent research has underscored the complex regulatory role of non-coding RNAs (ncRNAs) in regulating the GSH-GPX4 network, thus influencing cellular susceptibility to ferroptosis. This exhaustive review endeavors to probe into the multifaceted processes by which ncRNAs control the GSH-GPX4 network in ferroptosis. Specifically, we delve into the functions of miRNAs, lncRNAs, and circRNAs in regulating GPX4 expression and impacting cellular susceptibility to ferroptosis. Moreover, we discuss the clinical implications of dysregulated interactions between ncRNAs and GPX4 in several conditions, underscoring their capacity as viable targets for therapeutic intervention. Additionally, the review explores emerging strategies aimed at targeting ncRNAs to modulate the GSH-GPX4 pathway and manipulate ferroptosis for therapeutic advantage. A comprehensive understanding of these intricate regulatory networks furnishes insights into innovative therapeutic avenues for diseases associated with perturbed ferroptosis, thereby laying the groundwork for therapeutic interventions targeting ncRNAs in ferroptosis-related pathological conditions.